Determining the impact of directionality on road markings retroreflectivity using dynamic method - Babić, Dario; Ščukanec, Anđelko; Babić, Darko (Transport, 2018)
Road markings are an important component of delineation, intended to provide guidance and warning, to manage and regulate road traffic. In order to properly fulfil their function, road markings must be visible and it is precisely the visibility, in terms of road safety, that presents their most important characteristic. Practical tests showed that the marking visibility, or retroreflectivity, changes depending on directionality, showing higher values in the direction the marking is applied than in the opposite direction. This paper addressed the impact of road markings directionality on their retroreflectivity using the dynamic method for testing retroreflectivity. The research considered paint, thermoplastic and structural markings made of cold plastic. The results showed that the impact of directionality of paint and flat thermoplastic markings on their retroreflectivity is negligible. The average difference in retroreflectivity of renewed paint markings is 13.1 mcd/m2·lx and 11.85 mcd/m2·lx for existing paint markings, while the respective difference concerning flat thermoplastic markings is 9.60 mcd/m2·lx for renewed markings and 9.20 mcd/m2·lx for existing markings. A more significant difference was noted with structural markings made of cold plastic, namely 62.80 mcd/m2·lx for renewed markings and 49.60 mcd/m2·lx for existing markings. The results for paint and thermoplastic markings show that directionality should not be taken into consideration when evaluating their quality, which greatly facilitates and simplifies the process of testing the markings retroreflectivity. The stated results are of great importance for traffic safety and markings maintenance system.First Published Online: 4 Sept 2017